Remember when it rained: The elusiveness of gender discrimination in Indian school enrollment - Laura Zimmermann (Institute for the Study of Labor (IZA), 2012)
Indian girls have significantly lower school enrollment rates than boys. Anecdotal evidence suggests that gender-differential treatment is the main explanation, but empirical support is often weak. I analyze school enrollment using rainfall shocks, a plausibly exogenous source of income variation. Rainfall shocks matter most for young children and monotonically decline with age. Girls' school enrollment is more vulnerable to rainfall shocks than that of boys for 6-10 year olds, but there are no gender differences for older children. I argue that these results need to be interpreted carefully since they are a combination of two underlying effects, but propose that one explanation are age-specific forms of gender discrimination.
Keywords: D13; I21; J16; O12; O15; Q54; 330; rainfall; gender discrimination; school enrollment; education; India; Mädchen; Schulbesuch; Frauenbildung; Geschlechterdiskriminierung; Indien